Planar non-volatile memory based on metal nanoparticles - Kiazadeh, Asal (2011)
Resistive switching properties of silver nanoparticles hosted in an insulating polymer matrix (poly(N-vinyl-2-pyrrolidone) are reported. Planar devices structures using interdigitated gold electrodes were fabricated. These devices have on/off resistance ratio as high as 103 , retention times reaching to months and good endurance cycles. Temperature-dependent measurements show that the charge transport is weakly thermal activated (73 meV) for both states suggesting that nanoparticles will not aggregate into a metallic filament.